Online versus face-to-face cheating: The prevalence of cheating behaviours during the pandemic compared to the pre-pandemic among Turkish University students - Yazıcı, Sedat; Durak, Hatice Yildiz; Dünya, Beyza Aksu; Senturk, Burcu; Yazıcı, Sedat; Dünya, Beyza Aksu (Wiley, 2023)
Background During the COVID-19 period, academics and higher education institutions have shown deep concern about academic integrity related to measurement and evaluation issues that have arisen in online education. Objectives To address this concern, this paper examined the prevalence of cheating behaviour among university students before and during the pandemic by comparing self-reported cheating behaviours of students and academics' perceived levels of cheating behaviours of their students. Methods A correlational design was employed aligned with study objectives. Results and Conclusions The results indicate that although both groups reported a significant increase in cheating incidents in online education, instructors' perceived frequency of student cheating is remarkably greater than students' self-report cheating incidents. Contrary to the perceptions of instructors and stakeholders in education, students did not report a very drastic cheating increase in online education during the pandemic. The strongest predictive power for online cheating behaviours was the cheating behaviours in face-to-face education. Whereas the sensitivity of institutions and course instructors toward cheating behaviour was negatively associated with cheating behaviours in face-to-face education, this situational factor did not show a significant effect in distance education. Regarding individual factors, we found a significant relationship between cheating behaviours and gender, discipline, whereas no significant relationship was found in terms of student GPA. Consequently, in order to minimize the threats to the validity of scores associated with cheating, faculty should be supported through faculty development programs and resources so that they can develop authentic assessment strategies for measuring higher-order thinking skills.
Keywords: Academic Integrity; Cheating; Covid-19 Pandemic; Cyber Cheating; Online Cheating; Plagiarism